Analisis Pelaksanaan Supervisi Akademik dalam Peningkatkan Kinerja Guru Pada Sekolah Dasar di Kecamatan Masbagik - Nurdin, Nurdin; Muzakkar, Abdullah; Badarudin, Badarudin (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to describe the implementation of academic supervision by the principal and implemented by class teachers. The method used is a descriptive qualitative method. The data sources in this study are documents of academic supervision results carried out by the principal and learning administration documents prepared by teachers. This study was conducted at a Public Elementary School in Masbagik District, East Lombok Regency. Based on data analysis and research results, it can be concluded that the performance of the principal's academic supervision is carried out starting from preparation tasks, implementation, assessment, follow-up plans and reporting in the good and very good categories except for one principal who is still in the sufficient category. The implementation of the results of the principal's academic supervision of the 12 obligations of the learning process can be categorized as good, except for the use of learning media and LKPD (student worksheets) which still need to be improved so that they can improve the performance of teachers at Public Elementary Schools. in Masbagik District, East Lombok Regency.